2022
DOI: 10.1007/s10654-022-00933-x
|View full text |Cite
|
Sign up to set email alerts
|

Peto’s paradox revisited: black box vs mechanistic approaches to understanding the roles of mutations and promoting factors in cancer

Abstract: It is not often the case that scientific papers describing mathematical models of cancer, especially those including complex equations, can be described as "entertaining", but this is certainly the case for several seminal papers written by Richard Peto. The purpose of this short review is to revisit one such paper, written in 1984, entitled "The need for ignorance in cancer research" [1].In this particular article, which thankfully did not include the equations, Peto first discussed implications arising from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Uncovering the mechanistic links in both relationships (as partly done in this work with respect to childhood body size) will identify different pathways that could be modifiable and, together, could contribute a very substantial component of modifiable breast cancer risk. Another important consideration relating to mechanistic links is the distinction between mutagenesis and promoters in breast cancer causation 56 , which may also contribute to the differential effects of childhood adiposity and age at menarche on breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Uncovering the mechanistic links in both relationships (as partly done in this work with respect to childhood body size) will identify different pathways that could be modifiable and, together, could contribute a very substantial component of modifiable breast cancer risk. Another important consideration relating to mechanistic links is the distinction between mutagenesis and promoters in breast cancer causation 56 , which may also contribute to the differential effects of childhood adiposity and age at menarche on breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Tumours are initiated by clonal expansion of mutated somatic cells that have oncogenic potential, but the immediate subsequent steps that enable mutant cells to progress toward cancer in vivo remain unclear 2,3,4 . Mutations in oncogenes or tumour-suppressors genes reported to confer a cell with uncontrolled proliferative capacity and enhanced invasive properties in vitro , do not necessarily confer mutant cells with advantages that out-compete normal cells to form a tumour in vivo ; indeed, it is now clear that a permissive cellular and tissue environment is also necessary for tumour initiation 5, 6, 7 . Recent deep sequencing studies have revealed that a significant proportion of cells in healthy human epithelial tissues carry cancer-driving mutations that appear to have undergone clonal expansion but do not proceeded to form tumours 8, 9, 10, 11, 12, 13, 14, 15 .…”
Section: Introductionmentioning
confidence: 99%